MOTIVASI TENAGA KERJA BALI BEKERJA DI KAPAL PESIAR DISNEY CRUISE LINE - Putu Mira Astuti Pranadewi (Institut Pariwisata dan Bisnis Internasional, 2018)
The objective of this study are to encounter the level of Balinese labor motivation for working in Disney Cruise Line, determine the difference motivation for them who have not worked at the other cruise line company and who have experienced at cruise line before to work in Disney Cruise Line and also investigate the factors which motivate Balinese Labors for working in Disney Cruise Line. The factors in this study are working condition, compensation, company policy, change to have promotion and acknowledgement. In this research, there were 150 respondents selected as a sample using purposive sampling method. The instrument used is questionnaire data analyzed by confirmatory factor analysis and determinant analysis with SPSS program version 20.0. The findings of this research are the level of Balinese labor motivation to work in Disney Cruise LineÂ generally in average level, there are differences motivation between Balinese labor who have not worked at the other cruise line company and who have experienced at cruise line before to work in Disney Cruise Line in which the motivation level of inexperienced Balinese labors is higher than experienced ones, and the five factors in this study have their own influence to labors motivation, but the most strong factor is working condition factor and the weakest one is opportunity to have promotion. Â Key Words: Working Motivation, Balinese Labors Cruise Ship